Does the Quantity of Agricultural Mechanics Training Received as Secondary Students Affect Teacher Competency? - Mills, Denise; Anderson, Ryan G.; Paulsen, Thomas H. (Journal of Agricultural Systems, Technology, and Management, 2019)
The American Association for Agricultural Education’s National Research Agenda calls for research that clearly illustrates the factors that influence learning which are critical to advance education and student impact. Research priority area four of the American Association for Agricultural Education’s National Research Agenda calls for “meaningful, engaged learning in all environments” (Roberts, Harder, & Brashears, 2016, p. 37). Students are impacted by their experiences in the agricultural education classroom and laboratory, and examining and measuring teacher competence as well as its’ underlying components is a foundational piece of research which influences learning. The purpose of this study was to describe the perceptions of secondary agricultural education teachers concerning their personal competency to teach selected agricultural mechanics skills based on the quantity of agricultural mechanics training received at the secondary level. Individuals who have a higher perceived self-efficacy about a given skill feel differently and thus will act differently than those who do not, therefore Bandura’s theory of self-efficacy was used to guide this research. This descriptive study used a research-modified, paper-based questionnaire (N=130) and was part of a larger study. This study sought to determine the relationship between the quantity of agricultural mechanics training received at the secondary level and teachers' competency to teach those same competencies. The results indicated significant positive correlations in 53 of the 54 mechanics skill areas. The relationship between secondary agricultural mechanics courses completed and increased competency in agricultural mechanics should advise students considering future paths in agricultural education and agricultural mechanics to enroll in agricultural mechanics courses while at the secondary level.